The Effect of Hyperthermia on the Gene Expression of MDR1 and MRP4 Drug Efflux in Colorectal Cancer Cells - Z Ghorbani; M Heidari; M Jafarinia; M Rohani; A Akbari (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2020)
BACKGROUND AND OBJECTIVE: Hyperthermia has been reported as a new and adjunctive treatment of cancer in inhibiting DNA repair, increasing radiation sensitivity of cancer stem cells, increasing the sensitivity of drug-resistant cancer cells, and inhibiting cancer signaling pathways that cause apoptosis, suppression of cancer stem cell proliferation and disruption in cellular function. The aim of this study was to investigate the effect of hyperthermia on the gene expression pattern of drug resistance and cell survival. METHODS: In this in vitro study, two cell lines of human colorectal adenocarcinoma HT-29 and SW-48 were cultured. The cells of the hyperthermia and control groups were exposed to 42 or 43 °C and 37 °C for 2 hours, respectively. Then the effect of hyperthermia on cell survival was investigated by MTT method. The expression pattern of MDR1 and MRP4 genes was also measured using qRT-PCR. FINDINGS: Hyperthermia reduced cell survival, but this reduction was not significant. Hyperthermia decreased MDR1 gene expression in SW-48 cells (p=0.007). Although MDR1 expression in HT-29 cells was significantly reduced at 42 °C, no significant difference was observed between the hyperthermia and control groups. Hyperthermia also had no significant effect on MRP4 gene expression in SW-48 and HT-29 cell lines. CONCLUSION: The results showed that hyperthermia reduces the gene expression related to drug resistance, but has no significant effect on cell survival.